PrevaPrevalence of musculoskeletal disorders among heavy earth moving machinery operators exposed to whole-body vibration in opencast mininglence of musculoskeletal disorders among heavy earth moving machinery operators exposed to whole-body vibration in opencast mining - Mandal, Bibhuti B.; D. Manwar, Veena (International Journal Of Community Medicine And Public Health, 2017)
Background: Low back pain (LBP) and degenerative changes in the spinal system are reportedly associated with exposure to low frequency (0.5- 80 Hz) whole-body vibration (WBV). The main objective of the study was to determine prevalence of musculoskeletal disorders among Heavy Earth Moving Machinery (HEMM) operators exposed to WBV in an opencast mine in western India.Methods: Forty six operators from an opencast mine were recruited as exposed group in a questionnaire based cross-sectional study. Twenty eight employees engaged in sedentary office work were taken as control. All subjects were asked about location and severity of body pain in the past 7 days and 12 months. A four point pain scale was used. Significance of difference of demographic / anthropometric parameters was studied using t-test of independent samples. Association between the pain type and exposure was obtained using Chi-square test. Risk of each type of pain was determined in terms of odds ratio. Adjusted estimate of ORs were obtained through logistic regression modelling, wherein the model fitness was judged using Hosmer-Lemeshow test.Results: The mean exposure duration was 11.30 ± 7.45 years. LBP was the most predominant MSD which showed highly significant association with exposure (P <0.001). Overall, the risk analysis revealed a significant increase in the likelihood of MSD due to exposure. 39% of the exposed group required medical attention.Conclusions: Based on subjective response of exposed group, it can be said that prevalence of musculoskeletal pain as manifestation of MSD due to exposure to WBV especially LBP is high among HEMM operators which affected their quality of life.